Pre-service teachers’ experiences of schooling: Implications for preparation for inclusive education - Lee Rusznyak; Elizabeth Walton; Jacqueline Kenny (South African Journal of Education)
Teacher educators in South Africa face challenges of preparing new teachers for an inclusive education system that has been accepted as policy but is not yet fully realised in school contexts. Pre-service teachers entering teacher preparation programmes are themselves a product of a schooling system in which many inequalities and marginalising practices are still prevalent. In this article, we present an analysis of the extent to which pre-service teachers’ personal experiences within the schooling system influenced their perceptions about the benefits and drawbacks of 2 common organisational arrangements made for learners who experience barriers to learning. An analysis of empirical data from a questionnaire and individual interviews suggests that participants who had personally observed or experienced particular arrangements were more likely to hold fixed views about their potential benefits or drawbacks. We consider the implications of this finding for teacher education programmes that seek to produce teachers who can teach inclusively in the South African schooling system.